Hydrogen sulphide as a signalling molecule regulating physiopathological processes in gastrointestinal motility. (27th July 2017) - Jimenez, M; Gil, V; Martinez‐Cutillas, M; Mañé, N; Gallego, D
Abstract : The biology of H2 S is a still developing area of research and several biological functions have been recently attributed to this gaseous molecule in many physiological systems, including the cardiovascular, urogenital, respiratory, digestive and central nervous system (CNS). H2 S exerts anti‐inflammatory effects and can be considered an endogenous mediator with potential effects on gastrointestinal motility. During the last few years, we have investigated the role of H2 S as a regulator of gastrointestinal motility using both animal and human tissues. The aim of the present work is to review published data regarding the potential role of H2 S as a signalling molecule regulating physiopathological processes in gastrointestinal motor function. H2 S is endogenously produced by defined enzymic pathways in different cell types of the intestinal wall including neurons and smooth muscle. Inhibition of H2 S biosynthesis increases motility and H2 S donors cause smooth muscle relaxation and inhibition of propulsive motor patterns. Impaired H2 S production has been described in animal models with gastrointestinal motor dysfunction. The mechanism(s) of action underlying these effects may include several ion channels, although no specific receptor has been identified. At this time, even though there is much experimental evidence for H2 S as a modulator of gastrointestinal motility, we still do not have conclusive experimental evidence to definitively propose H2 S as an inhibitory neurotransmitter in the gastrointestinal tract, causing nerve‐mediated relaxation.